INFLUENCE OF LEADERSHIP, COMPENSATION & COMMITMENT TO EMPLOYEE PERFORMANCE IN PASAR MOBIL KEMAYORAN MANAGEMENT (PPMK) - Herdina Irdaningsih; Parwoto Parwoto; Ahmad Badawi Saluy (Dinasti International Journal of Education Management And Social Science, 2020)
This study aims to examine and analyze the effect of leadership, compensation, commitment, and career development on employee performance at the Pasar Mobil Kemayoran Management (PPMK). In this study, the authors used a descriptive research method using a quantitative approach. In this study, the ordinal measurement method uses a Likert scale which is used to measure the attitudes, opinions and perceptions of a person or group of people about social phenomena. Based on the results of the study showed that the value of Fcount is 11,644 with sig. of 0,000 while the value of Ftable of 2.38. Because Fcount is greater than Ftable (11,644> 2.38) and the value of sig. 0,000 <0.05 then H0 is rejected and Ha is accepted, so it can be concluded that the leadership variable (X1).